Naturally Occurring Bioactives as Antivirals: Emphasis on Coronavirus Infection - Ayatollahi, Seyed Abdulmajid; Sharifi-Rad, Javad; Tsouh Fokou, Patrick Valere; Mahady, Gail B.; Ansar Rasul Suleria, Hafiz; Krishna Kapuganti, Shivani; Gadhave, Kundlik; Giri, Rajanish; Garg, Neha; Sharma, Rohit; Ribeiro, Daniel; Rodrigues, Célia F.; et al. (Frontiers in Pharmacology, 2021)
The current coronavirus disease (COVID-19) outbreak is a significant threat to human health and the worldwide economy. Disappointingly, even after more than a decade of intensive research on coronaviruses, there are still no licensed effective vaccines or treatments available for them. This suggests an urgent need to find specific medicines and/or vaccines. Coronaviruses cause a variety of diseases, such as pneumonia-like upper respiratory tract illnesses, gastroenteritis, encephalitis, multiple organ failure involving lungs and kidneys which might cause death. Specifically, the current COVID-19 infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has claimed more than 9 million reported cases and half a million deaths globally. SARS-CoV-2 is easily transmitted from person-to-person and has spread quickly across all continents. With the alarmingly increasing morbimortality rates caused by COVID-19 and damage to the global economy, there is an urgent need for effective prevention and treatment strategies. Since we are still within the ongoing COVID-19 pandemic, scientists are struggling on investigating the effects of available substances/drugs/vaccines that may be effective against SARS-CoV-2, with some natural products revealing successful effects in fighting several viral infections. Indeed, as they are components of diet or are prepared as dietary supplements people might consider them safer than synthetic products. As an example, Traditional Chinese Medicines have been effectively applied in SARS-CoV-2 infected patients with promising results. Thus, here we aimed to review the therapeutic potential of plant products for the treatment of several viral infections, with special emphasis on SARS-CoV-2 infection. Realistic strategies that can be employed for the effective use of bioactive compounds for anti-SARS-CoV-2 research are also provided.